Penerapan Manajemen Strategik Menggunakan Analisis SWOT di SMP Muhammadiyah 1 Berbah Sleman - Heni Nadia Fitriana (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2024)
This article focuses on the implementation of strategic management using SWOT analysis at SMP Muhammadiyah 1 Berbah. The study aims to explore the implementation of strategic management in the school and provide strategy recommendations based on strengths, weaknesses, opportunities, and threats (SWOT) analysis. Data were collected through observation and interviews with the principal of school, and teachers. The findings were analyzed using the SWOT analysis method and IFAS/EFAS calculations that help identify internal and external factors that affect school performance. This research emphasizes the importance of effective strategic management in achieving educational goals and maintaining competitiveness. The results of the analysis can be valuable input for formulating recommended strategies to capitalize on strengths, address weaknesses and take advantage of opportunities while mitigating threats. The results of this study show that strengths have a total value of 3,7 inversely proportional to weaknesses with a total value of 0,65. The company's position has opportunities with a total value of 4 compared to threats with a total value of 1,7. According to the SWOT analysis calculation, the highest value is obtained from the Strenght-Opportunities combination with a value of 7,7.